2015
DOI: 10.1039/c5tc00394f
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule magnets grafted on gold: magnetic properties from ab initio molecular dynamics

Abstract: The computational characterization of the single molecule magnet (SMM) [Fe 4 (AcS(CH 2 ) 5 C(CH 2 O) 3 ) 2 (dpm) 6 ] (Fe 4 C 5 ) with Ac = CH 3 CO and Hdpm = dipivaloylmethane, grafted on the Au(111) surface (Fe 4 C 5 @Au (111)) is presented. For the first time, ab initio molecular dynamics (AIMD) calculations have been used to study the evolution of the structural properties of a SMM once adsorbed on a metallic substrate. Important structural rearrangements induced by the grafting process can be observed than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 47 publications
6
37
0
Order By: Relevance
“…Such a finding is not fully unexpected, though not detected in X‐ray absorption experiments. Indeed, ab initio molecular dynamics calculations showed that Fe 4 molecules chemically grafted on a gold surface can access several configurations with similar energy . The differences in the geometrical parameters of such configurations are comparable with those estimated from Mössbauer spectra and significantly affect important SH parameters, such as J values and single‐ion anisotropies.…”
Section: Towards Single Molecule Addressing Of Fe4 and Related Systemssupporting
confidence: 52%
See 1 more Smart Citation
“…Such a finding is not fully unexpected, though not detected in X‐ray absorption experiments. Indeed, ab initio molecular dynamics calculations showed that Fe 4 molecules chemically grafted on a gold surface can access several configurations with similar energy . The differences in the geometrical parameters of such configurations are comparable with those estimated from Mössbauer spectra and significantly affect important SH parameters, such as J values and single‐ion anisotropies.…”
Section: Towards Single Molecule Addressing Of Fe4 and Related Systemssupporting
confidence: 52%
“…Especially relevant to the present Microreview are R groups that allow to promote and control chemisorption on metals, , , , or carbon substrates, from solution. For R = (CH 2 ) n SAc, a fine control of molecular orientation on Au(111) was achieved by tuning the length ( n ) of the spacer unit between the Fe 4 core and the surface‐binding terminations, as detailed below , , . However, some 3 R complexes are also suitable for electrospray deposition (ESD) or even thermal sublimation in UHV.…”
Section: Chemistry Of Fe4 and Related Complexesmentioning
confidence: 99%
“…Indeed, although its relatively small intensity, this property happens to be rapidly modulated by the FeOFe degree of freedom, which has been demonstrated to vary of several degrees due to thermal fluctuations [38,39], and thus opening a possible efficient relaxation pathway.…”
Section: Magneto-structural Correlationsmentioning
confidence: 99%
“…The results presented in the work highlight a possible relevant role of the anisotropic interaction in the SMMs relaxation processes. Indeed, although its relatively small intensity, this property happens to be rapidly modulated by the FeOFe degree of freedom, which has been demonstrated to vary of several degrees due to thermal fluctuations [38,39], and thus opening a possible efficient relaxation pathway. …”
Section: Magneto-structural Correlationsmentioning
confidence: 99%